Strategi Dakwah Kultural melalui Media Tradisional dalam Keberlanjutan Tradisi Keagamaan di Kota Langsa - Wildan, T.; Gandhi, Al Mutia (Anida (Aktualisasi Nuansa Ilmu Dakwah), 2025)
This study investigates the role and sustainability of traditional media in Islamic religious practices in Langsa City, Aceh, amidst the pressures of modernization and digital media penetration. It aims to understand the functions, challenges, and adaptation strategies of traditional media, as well as intergenerational community perceptions towards it. Employing a descriptive qualitative approach, data were collected through in-depth interviews with 15 key informants, participatory observation, focus group discussions (FGDs), and document studies, and then analyzed thematically. The findings reveal that traditional media (such as Meugang, Seudati Dance, and Saman) continue to play a central role as a means of religious expression, cultural communication, and strengthening social cohesion. However, their sustainability faces serious challenges, including a decline in regeneration among young practitioners, weak policy support, and competition with digital media. In response, communities have developed adaptation strategies such as content digitization and integration into education, although this raises dilemmas between preserving authenticity and commodification. The study concludes that the continuity of traditional media depends on contextual adaptive abilities that blend local values with innovations in format and medium. These findings contribute to the studies of cultural communication and media ecology and recommend the need for supportive policies, cultural education, and a gender-inclusive approach for revitalization. Further research with a broader ethnographic scope is suggested.